Current treatment practices and efficacy in solar urticaria: insights from a patient survey - Kiefer, Lea; Aulenbacher, Felix; Terhorst-Molawi, Dorothea; Giménez-Arnau, Ana M.; Gonçalo, Margarida; Fukunaga, Atsushi; Kocatürk Göncü, Emek; Kulthanan, Kanokvalai; McSweeney, Sheila; Röckmann, Heike; Weller, Karsten; Rhodes, Lesley E.; et al. (Frontiers in Immunology, 2025)
BackgroundSolar urticaria (SolU) is a rare chronic inducible urticaria and photodermatosis, presenting with wheal/flare formation accompanied by severe itch, following exposure to light in the triggering action spectrum. Therapeutic options remain limited for SolU, and the perspective of patients regarding the efficacy of available treatments remains unknown.MethodsPatients with SolU, organized in a disease-specific Facebook group, were asked to complete an electronic questionnaire on their condition and therapies performed between May 2023 and April 2024. The certainty of SolU diagnosis was differentiated as i) physician confirmed by clinical presentation, ii) light provocation tests, or iii) patient-reported. Study outcomes included clinical presentation, triggering action spectrum, disease severity, impairment of quality of life, therapies performed, and their efficacy. Logistic regression models were used to study the association between clinical factors and treatment outcomes.ResultsA total of 112 patients (female, n = 94; median age, 42 years) participated in the study. Most patients considered their condition severe or extremely severe (n = 72, 76.6%) with a very/extremely impacted quality of life (n = 82, 86.3%). The majority of patients received non-sedating antihistamines (58.9%, n = 66), leading to worsening, no change, or only slight improvement in most cases (82.2%, n = 53). Omalizumab was given to 28 patients and induced complete control in 32.1% of cases. Treatments with sedating antihistamines, ciclosporin, systemic corticosteroids, phototherapy, and Polypodium leucotomos were performed in a residual number of patients and did not lead to a substantial improvement of the symptoms. Antihistamines were more effective in patients with mild disease, whereas omalizumab maintained a positive response across different disease severity levels.ConclusionSolU is generally perceived as severe by affected patients, leading to a high impairment of quality of life. Performed therapies, including off-label treatments, are not sufficient to reach complete remission of symptoms in the majority of patients. Effective therapeutics for SolU are urgently needed to achieve better care for this highly burdened patient population.